Climate-Induced Migration and the Challenges of Food Insecurity in Nigeria - Odebunmi, Ramon Odunayo; Adesida, Bright (African Journal of Stability and Development (AJSD), 2025)
This study aims to examine climate-induced migration and the challenges of food insecurity in Nigeria. It also seeks to analyse further how climate-induced migration leads to food insecurity. Climate change has severe impacts on human survival and natural habitats, causing loss of soil fertility, habitat destruction, and natural disasters such as wildfires, cyclones, landslides, flooding, rising sea levels, and earthquakes. One negative effect of climate change is migration, which occurs as people flee extreme weather conditions. The main point of this paper is that climate-induced migration does not always result in food insecurity. However, this relationship is influenced by conflicts between farmers and pastoralists and by the limited capacity of the government to implement effective policies and programmes to resolve ongoing disputes between migrants and host communities. Persistent clashes between pastoralists and local communities continue to threaten food production in Nigeria, driven by recurring herdsmen attacks, kidnappings, and the victimisation of farmers. This study used a qualitative approach, relying on existing literature and datasets. It employs the Environmental Scarcity Theory and Securitisation Theory as its theoretical framework. The conclusion is that while food insecurity can be a consequence of climate-induced migration, this link is intensified by conflicts between pastoralists and farmers and the Nigerian government’s failure to address these disputes through effective policies that prevent resource conflicts between host communities and pastoralists.